RNA m1A Methyltransferase TRMT6 Predicts Poorer Prognosis and Promotes Malignant Behavior in Glioma - Wang, Beibei; Niu, Lihua; Wang, Zhengyang; Zhao, Zhihua (Frontiers in Molecular Biosciences, 2021)
Abstract: Background: Glioma is the most prevalent central nervous system tumor in humans, and its prognosis remains unsatisfactory due to a lack of effective therapeutic targets. The ectopic expression of N1-methyladenosine (m1A) regulators is a key participant in tumorigenesis and progression. However, the m1A regulators expression status, prognostic value and relationship with tumor clinical features in glioma remain unclear. Methods: Public datasets were used to analyze the mRNA and protein expression levels of m1A regulators. Kaplan–Meier and Cox regression analyses were performed to confirm the prognostic value of m1A regulators in glioma. Cellular experiments were conducted to verify the effect of TRMT6 on cell function. A comprehensive bioinformatic analysis was conducted to identify the potential molecular mechanisms regulated by TEMT6 in glioma. Results: We found that the dysregulation of m1A regulators was closely associated with tumorigenesis and progression in glioma. Furthermore, TRMT6 might be a powerful and independent biomarker for prognosis in glioma. Our study showed that inhibition of TRMT6 suppressed the proliferation, migration and invasion of glioma cells. Mechanistically, TRMT6 may be involved in glioma progression by regulating cell cycle, PI3K-AKT, TGF-beta, MTORC1, NOTCH and MYC pathways. Conclusions: Variation in m1A regulators was closely associated with malignant progression in glioma. Silencing TRMT6 suppressed the cell proliferation, migration and invasion in glioma. m1A regulators, especially TRMT6, might play an essential role in the malignant progression of glioma.